2021
DOI: 10.3390/antiox10050639
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Frozen and Freeze-Dried Drone Brood Homogenate Regarding the Stage of Larval Development

Abstract: Drone brood is a little-known and poorly studied bee product used and valued in the treatment of many diseases, including male infertility and women’s menopausal disorders. The aim of this study was to evaluate the antioxidant activity of drone brood depending on the stage of larval development and the method of preservation. Aqueous and ethanolic homogenate extracts of drone brood were assayed for antioxidant activity (with the DPPH, FRAP, and ABTS methods), polyphenol, and flavonoid content. The extracts’ po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Drone brood was more than 50% active than that of the royal jelly. Using both, DPPH and FRAP methods, the highest values were obtained for 11-day-old DB, which is in agreement with our earlier study [24].…”
Section: Antioxidant Activity Determinationsupporting
confidence: 92%
See 1 more Smart Citation
“…Drone brood was more than 50% active than that of the royal jelly. Using both, DPPH and FRAP methods, the highest values were obtained for 11-day-old DB, which is in agreement with our earlier study [24].…”
Section: Antioxidant Activity Determinationsupporting
confidence: 92%
“…Such observation was done for the first time. According to earlier reports, some flavonoids were expected [ 24 , 34 , 46 ] and tested (naringenin, apigenin, chrysin, sakuranetin) there are certain flavonoids: flavanones (hesperetin, naringenin), flavones (apigenin derivatives), and isoflavonoids (genistein, formononetin, coumestrol), as well as ferulic acid present in royal jelly. However, there are no polyphenol profiles available for the drone brood.…”
Section: Discussionmentioning
confidence: 95%
“…However, Tomczyk et al [19] analyzed the phenolic profile of Polish honeys, showing orange, blue, yellow, and green bands in rape honey. The composition of polyphenols in drone brood was similar to that in the previous studies [14,15]. Blue bands dominated in the drone brood homogenate chromatogram, which proves the presence of ferulic acid (Rf Fig.…”
Section: The Comparison Of the Hptlc Polyphenolic Profiles Of Drone B...supporting
confidence: 85%
“…The flavonoid content varied depending on the larval development stage, from 25.7 mg/ 100 g in 7-day-old larvae to 94 mg/100 g in 11-day-old larvae. [13] The flavonoid content also differed among the developmental stages of larvae, pupae, and adults, which were 5.8, 4.7, and 4.5 mg/g, respectively. [12] Sidor et al reported that the total flavonoids in apilarnil were 9.27 %, lower than the 11.3 % in royal jelly.…”
Section: Total Lipid Contentmentioning
confidence: 94%
“…The ideal approach, however, is freeze-drying, which keeps the biologically active components in the drone brood for a long time. [7] Apilarnil also has biologically active substances that contribute to many pharmacological effects, such as antioxidant, [13] neuroprotective, anti-apoptotic, [14] anti-inflammatory and androgenic effects. [10,[14][15][16] According to the literature, apilarnil is very good at fighting oxidation because it has a lot of polyphenols.…”
Section: Introductionmentioning
confidence: 99%